Melanin concentrating hormone modulates oxytocin-mediated marble burying - Sanathara, Nayna M. (Neuropharmacology, 2017)
Repetitive and perseverative behaviors are common features of a number of neuropsychiatric diseases such as Angelman’s syndrome, Tourette’s syndrome, obsessive-compulsive disorder, and autism spectrum disorders. The oxytocin system has been linked to the regulation of repetitive behavior in both animal models and humans, but many of its downstream targets have still to be found. We report that the melanin-concentrating hormone (MCH) system is a target of the oxytocin system in regulating one repetitive behavior, marble burying. First we report that nearly 60% of MCH neurons express oxytocin receptors, and demonstrate using rabies mediated tract tracing that MCH neurons receive direct pre-synaptic input from oxytocin neurons. Then we show that MCH receptor knockout (MCHR1KO) mice and MCH ablated animals display increased marble burying response while central MCH infusion decreases it. Finally, we demonstrate the downstream role of the MCH system on oxytocin mediated marble burying by showing that central infusions of MCH and oxytocin alone or together reduce it while antagonizing the MCH system blocks oxytocin-mediated reduction of this behavior. Our findings reveal a novel role for the MCH system as a mediator of the role of oxytocin in regulating marble-burying behavior in mice.